(untitled) (Annals of Medical Research, 2021)
Aim: We investigated the diagnostic and prognostic utility of MUC-1, MUC-4, CDX2 and OCT-1 expression profiles in high-mortality gastric carcinomas and their precancerous lesions.Material and Methods: Areas in proximity of dysplasias and gastric carcinomas that were suspected of having intestinal metaplasia were stained with PAS / Alcian Blue at pH 2.5 and pH 0.5; Giemsa staining was applied for evaluation of presence of H. Pylori.Results: Presence of MUC-1 expression may exclude the diagnosis of low-grade dysplasia. MUC-1 and MUC-4 overexpression may be used for determination of groups at high risk of development of carcinomas, primarily in cases of high-grade dysplasia, while overexpression of MUC-1 in gastric carcinomas may be used as a favorable prognostic factor. Presence of CDX2 expression in various histological types of carcinomas gives rise to a suggestion that intestinal differentiation occurs in all histological types at least to some degree. OCT-1 plays a role in CDX2-mediated carcinogenesis and its regulation. Conclusion: In cases of dysplasia occurring with intestinal metaplasia, CDX2 was found to be expressed at a significantly higher degree (95.5%, p=0.011). Expression of CDX2 and OCT-1 was observed in all high-grade dysplasia cases, and was significantly higher in comparison to low-grade dysplasia cases (p=0.042; p=0.006, respectively). MUC-1 and MUC-4 expression significantly increased with each progressing stage of precancerous lesions in all lesions following low-grade dysplasia (p=0.0001; p=0.027, respectively). MUC-1 expression was the lowest (53.6%) in weak cohesive type carcinomas. Positive immunoreactivity with MUC-1 and CDX2 was higher in cases with a smaller number of metastatic lymph nodes compared to the cases with a larger number thereof.